Discussion in Pinang Malaysia: Community Empowerment of Village Tourism Development - Posma Sariguna Johnson Kennedy (Jurnal Pengabdian West Science, 2023)
Village Tourism is a comprehensive concept encompassing attractions, facilities, community, and tourism aspects to enhance village well-being and cultural appreciation through various tourism forms. Principles involve local empowerment, economic growth, community involvement, and technology use. It adheres to sustainability, creativity, efficiency, social justice, and environmental awareness. The goal is economic growth while preserving culture. Functions include cultural preservation, community-based tourism, and education. Effective strategies, government roles, and stakeholder involvement are essential for sustainable village tourism. The activity involved visiting Disted College, George Town, Malaysia, to deepen my understanding of village tourism through discussions with academic expert Professor Vikneswaran Nair. Responsible rural tourism preserves the environment and culture and provides socio-economic opportunities. Successful and unsuccessful case studies from various Asian countries are analyzed to learn about future responsible rural tourism development.